Newly diagnosed atrial fibrillation detected by noninvasive screening methods in clinical practice - Luis Aguinaga, MD, MBA, PhD, RMFAC, FACC, FESC; Walter Bernal, MD; Alejandro Bravo, MD; Raúl Weiss, MD; Leonardo Pilon, MD; Gabriela Reyes, MD; Domingo Pozzer, MD; Alejandro Polti, MD; Daniel Ortigoza, MD; Verónica Tapia, MD; Paola Naput, MD; Sofía Guardiet, MD; et al. (Heart Rhythm O2)
Background: Patient characteristics and outcomes of newly diagnosed atrial fibrillation (AF) have been investigated in large registries. Objective: The study aimed to address the role of non-invasive screening tools in diagnosing AF in the Argentinian clinical practice. Methods: This was an observational retrospective study. Patients’ clinical characteristics and management of newly diagnosed AF detected by a non-invasive screening tool were analyzed. Results: Of 12,635 AF outpatients, 1018/5947 (17.1%) of newly diagnosed AF were detected by a screening method: electrocardiography monitoring device (82.3%), self-pulse palpation (17.3%), and smartwatch/smartphone (0.4%).Screening (+) patients were older (73 years [63–81] vs 72 [65–81], P = not significant) and had a higher prevalence of ≥ 75 year-old patients (45.5% vs 37.9%, P < .001) and women (42.5% vs 41.2%, P = not significant).Adjusted results (odds ratio [95% confidence interval]) by multivariate analysis showed that alcohol consumption (1.74 [1.14–2.65]), thyroid dysfunction (1.26 [1.07–1.49]), coronary artery disease (1.40 [1.19–1.64]), paroxysmal AF (2.39 [1.94–2.96]), asymptomatic condition (2.44 [2.07–2.86]), high risk of thromboembolic and bleeding complications (CHA2DS2-Vasc, 1.18 [1.06–1.32] and HASBLED, 1.25 [1.08–1.46]), and heart failure (1.23 [1.01–1.49]) were associated with screening (+) patients. Although no difference in the oral anticoagulation therapy was detected, vitamin K antagonists were less frequently prescribed (0.66 [0.53–0.82]). Electrical cardioversion was preferred over class I and III antiarrhythmic drugs (1.33 [1.07–1.66] vs 0.61 [0.44–0.84] and 0.79 [0.64–0.97]). Conclusion: Non-invasive screening tools are mainly used in Argentinian clinical practice to detect AF in asymptomatic patients at high risk of thromboembolic and bleeding complications. Vitamin K antagonists are less prescribed, and electrical cardioversion is preferred over antiarrhythmic drugs for initial rhythm control.